EKSPLOITASI SEKSUAL TERSELUBUNG TERHADAP PEREMPUAN DI SEKTOR INFORMAL DI INDONESIA - Rusmana, I Putu Edi; I Gusti Agung Kiddy Zulkarnain; I Made Fajar Pradnyana; I Gede Sadia Dwi Ratmaja (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study aims to analyze the various forms of hidden sexual exploitation of women in Indonesia’s informal sector and to examine the ideal model of legal protection for victims from a criminal law perspective. This phenomenon emerges as a result of gender inequality, patriarchal structures, and economic pressures that place women in subordinate and vulnerable positions susceptible to abuse of power. Within informal labor relations, women are often exploited through seemingly legitimate service or employment arrangements that conceal coercive or manipulative practices. In Indonesia’s positive law, Law No. 21 of 2007 on the Eradication of Human Trafficking and Law No. 12 of 2022 on Sexual Violence do not explicitly address covert or non-physical forms of sexual exploitation occurring in informal work environments. This study employs a normative legal research method through statutory, conceptual, and case approaches. The findings reveal a normative vacuum and insufficient legal protection for women in the informal sector, caused by a positivistic and gender-neutral orientation in criminal law. Therefore, a comprehensive criminal law reform is urgently required—one that is gender-sensitive, human rights-based, and oriented toward substantive justice. This research contributes conceptually to the development of a more responsive and humanistic criminal law system that recognizes structural inequality and protects women from hidden sexual exploitation in informal labor contexts.